THE EFFECT OF USING PREFABRICATED VERTICAL DRAIN (PVD) ON TILTED BUILDINGS - Desy Rahmayanti (Lambung Mangkurat University Press, 2014)
As high-rise buildings continue to grow in number, the availability of land for such development shrinks. This has led to those buildings being constructed in very close proximity of each other. This can be a problem in areas with soft soil, such as Banjarmasin. It is apparent from the fact that those buildings lean toward each other quite shortly after they have been constructed, in such a way that they become structurally unstable. This research aims at finding a solution for this problem. In this research the Soft Soil Creep (SSC) was used to model soil. The parameters include modified compression index (λ*) = 0.13, modified swelling index (κ*) = 0.03, and the secondary compression index (μ*) = 0.029 obtained from soil sampled in Banjarmasin at the Trisakti Port. The value of Cc is 0.9817 , Cs is 0.132 and Cα is 0.176 with vulnerable void ratio (e0) of 1,9-2,3. The simulation suggest that the problem can be solved using a combination of vertical drain and applying a particular amount of load in form of a soil heap on the side opposite that the building is tilted to. It is found the slope can be reduced significantly after only 4 years (U=2.5%). The use of PVD up to 21 meters deep without a soil heap is unable the restore the building to its initial verticality. Hence, it takes a combination of the load and the vertical drain to obtain maximum results. The combined results produce a faster time in restoring the buildings verticality from ± 4.5 years to only ± 3 months.